1999
DOI: 10.1046/j.1365-2222.1999.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators in bronchoalveolar lavage samples from children with and without asthma

Abstract: Elevated histamine concentrations were found in children with wheeze regardless of the aetiology, whereas ECP was only elevated in those asthmatics with atopy. This suggests that even in relatively quiescent periods, there is some on going activation of airway eosinophils in children with atopic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 11 publications
1
36
1
Order By: Relevance
“…Over the past few years flexible fibreoptic bronchoscopy has been used with increasing frequency and become an important tool in the investigation of infants and children with airway disease [5][6][7][8][9][10]. Using this technology, the present study has shown that the eosinophil-activating chemokines RANTES, MCPs-3 and -4, and eotaxins-1 and -2 are associated with the recruitment of eosinophils into the airways of asthmatic children.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Over the past few years flexible fibreoptic bronchoscopy has been used with increasing frequency and become an important tool in the investigation of infants and children with airway disease [5][6][7][8][9][10]. Using this technology, the present study has shown that the eosinophil-activating chemokines RANTES, MCPs-3 and -4, and eotaxins-1 and -2 are associated with the recruitment of eosinophils into the airways of asthmatic children.…”
Section: Discussionmentioning
confidence: 81%
“…In a separate study, analysis of induced sputum from children with acute asthma revealed that neutrophil inflammation is often associated with acute exacerbations while eosinophil infiltration is a reflection of the chronicity of the disease [14]. Although the mechanisms by which neutrophils are recruited are not fully understood, airway neutrophilia has been associated with the release of the potent neutrophil attractants IL-8 and leukotriene (LT)B 4 [9,13,14]. Similarly, it has previously been shown that IL-8 is associated with neutrophil activation in virus-induced exacerbations of asthma [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with chronic cough, without wheeze, due to cough variant asthma should exhibit airway inflammation similar to known atopic asthmatics, who have increased eosinophils and mast cells in their bronchoalveolar lavage fluid (BAL) [11] and increased concentrations of eosinophil cationic protein (ECP) and histamine in BAL [12]. The aim of the present study was to investigate the cell composition and inflammatory mediators within the airways of children with chronic cough and compare the results with the population of normal nonatopic children and atopic asthmatics, who had undergone lavage for both this and previous studies.…”
mentioning
confidence: 99%
“…In one of these studies a nonbronchoscopic procedure was used to collect BAL fluid from children undergoing surgery under a general anesthetic (5). Further studies from this group showed that eosinophil cationic protein (ECP) levels were significantly higher in BAL fluid collected during asymptomatic periods from subjects with atopic asthma than in normal control subjects (6). This suggests that in the airway eosinophils in children with atopic asthma are activated even in the absence of ongoing clinical symptoms.…”
Section: What Do We Know?mentioning
confidence: 97%